Assessment of Climate Change Impacts on the Future Hydrologic Cycle of the Han River Basin in South Korea Using a Grid‐Based Distributed Model†. (17th April 2016) - Ahn, So Ra; Kim, Seong Joon
Abstract: The purpose of this study is to assess the impacts of climate change on the hydrologic cycle of the Han River Basin in South Korea using the Projection of Hydrology via the Grid‐based Assessment for Climate Change (PGA‐CC) model. PGA‐CC is a physically based continuous, long‐term, distributed model. The model was calibrated and validated using 9 years (2001–2009) of inflow data from two sub‐basins to reservoirs (the Chungju Reservoir and Soyang Reservoir) in the Han River Basin with a 4 km spatial resolution. The average Nash–Sutcliffe model efficiencies of the Chungju and Soyang reservoirs were 0.57 and 0.71, and the average coefficients of determination were 0.65 and 0.72, respectively. The applicability of the PGA‐CC model was tested by assessing the future river basin hydrology with the HadGEM3‐RA AR5 4.5 and 8.5 climate change scenarios. The annual total discharge from the RCP 4.5 scenario in the 2080s showed a change of up to +33.0% based on the 1070 mm yr −1 value from the baseline period (1980–2009) due to a +28.1% increase in precipitation. The annual evapotranspiration from the RCP 8.5 scenario showed an increase of up to 46.2% compared to the baseline period of 357 mm yr −1 due to a temperature increase of 5.4 °C. Copyright © 2016 John Wiley & Sons, Ltd.